ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG PADA MASA PANDEMI COVID-19 - Sotya Fevriera; Efita Pataniho (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to explain the effect of the production quantity, the amount of capital, the capital source and the number of workers on the income of corn farmers in Pediwang Village, North Kao District, North Halmahera Regency. This research was conducted during the Covid-19 pandemic using primary data collected by interview. The data analysis method used is the multiple nonlinear regression analysis estimated using ordinary least square (OLS) method and robust standard error. This study found the quantity of corn production type 3 (pipilan) has a significant positive effect on the income of corn farmers and that the capital value has a significant negative effect on the income of corn farmers. The quantity of corn type 1 (fruit), the quantity of corn type 2 (couples), the capital aid from the government, the capital aid from other sources than the government and the number of workers have no significant effect on the income of corn farmers.